Gender and relationships : a practical action kit for young people (Commonwealth Secretariat LondonGB, 2001)
Seeks to raise awareness of the importance of gender issues in sexual and reproductive health and to provide practical ideas for introducing gender awareness into existing youth programmes. Explains what gender is and how it affects relationships and sexual and reproductive health.
Keywords: GENDER ROLES